Translating cognitive science in the public square. Issue 10 (October 2021) - Hassinger-Das, Brenna; Zosh, Jennifer M.; Bustamante, Andres S.; Golinkoff, Roberta Michnick; Hirsh-Pasek, Kathy
Abstract : Public space interventions offer one example of how to translate cognitive science into the public square. Here, we detail several successful projects and the six principles of learning that underlie them that support caregiver–child engagement, interaction, and the use of content area–specific language. Policy and community implications are also discussed.